THE ROLE OF THE AGRICULTURAL SECTOR IN THE ECONOMY OF WEST JAVA PROVINCE FOR THE 2010-2019 PERIOD - Achmad Tjahja Nugraha; Titik Inayah; Indria Agita Setyowati (Syarif Hidayatullah State Islamic University Jakarta, 2022)
The agricultural sector of West Java Province has a strategic function as a national food barn and supports the needs of basic foodstuffs, especially rice. However, on the other hand, the production of rice and most of the agricultural sector commodities of West Java Province continues to decline. It aims to analyze the contribution of the agricultural sector and the agricultural subsector. Analyze and classify the position of the agricultural subsector. Analyze and classify the growth and competitiveness of agricultural subsectors. Analyze and identify the agricultural subsectors that are being developed. The data analysis consists of Contribution Analysis (Share), Klassen Typology Analysis, Shift Share Analysis, Static Location Quotient Analysis, and Dynamic Location Quotient Analysis in the period of research analysis, namely 2010-2019. The results showed that the overall agricultural sector contribution was 8.11%, the largest contribution was the food crop subsector 3.69%, horticultural crop subsector 1.58%, livestock 1.06%, fisheries 0.85%, plantation crops 0.73%, and the smallest forestry 0.08%. The food crops and horticultural crops subsector is positioned as an advanced but depressed subsector, while the plantation, livestock, forestry, and fisheries subsector as a subsector is relatively lagging. The fisheries subsector has faster growth, while the food crops, horticultural crops, plantation crops, animal husbandry, and forestry subsectors have slower growth, and the entire agricultural subsector has less competitiveness. The food crops and horticultural crops subsector is the leading subsector, but all agricultural subsectors have the potential for slower development in the future. The results of this study are expected to be input and consideration for the West Java Provincial Government in developing policies related to agricultural development.